Carbon footprints of large compression chillers for district cooling – accounting for temporal resolution of the electricity supply - Weber, Rosa; Rixrath, Doris; Schauer, Raphael; Krail, Jürgen; Piringer, Gerhard (International Conference “Environmental Engineering”, 2023)
Compression chillers are a common technology used in district cooling networks, with fluctuating cooling loads and consuming different electricity mixes at different times. This work aims to study these effects on the CFs of operating three compression chillers in a district cooling plant in Austria, using LCA-based CF modelling. Electricity consumption dominates the chillers’ CFs. While using the annual average electricity mix overestimated the CF for two warm-season and mixed-season chillers by 12% and 1%, respectively, it underestimated the CF for a mainly cold season chiller by 6%. Seasonal changes in electricity mixes and cooling loads were well suited to explain the calculated CF deviations and should be accounted for in carbon footprints dominated by renewables-rich electricity consumption.
Keywords: district cooling; compression chillers; carbon footprint; electricity mix; temporal resolution